Mental Zooming as Variable Asset Integration in Inter-temporal Choice - Stein T. Holden; Dag Einar Sommervoll; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2020)
Our time preferences deviate systematically from that of Homo economicus. They seem to be driven by a form of mental zooming, where higher and more distant payouts induce a more holistic perspective in contrast to smaller and near future payouts. We model zooming as variable asset integration and ask whether this can explain the observed variation in discount rates in experiments. It can. Equally important, the zooming for both time and magnitude is similar across two countries (Ethiopia and Malawi), and within a country (Ethiopia). An intriguing empirical regularity is that the dimensionless degree of zooming in time is roughly twice the zooming degree in magnitude. We offer no explanation for this asymmetry between time and magnitude.
Additional information: The paper is part of the NORGLOBAL2 project "Youth Business Groups for Sustainable Development: Lessons from the Ethiopian Model", and it aims at providing a better basis for understanding investment decisions by youth group members.
Keywords: C93; D03; D91; 330; time discounting; magnitude effects; asset integration; zooming theory